GE_GERICHTE P/1729/2013 vom 2. Dezember 2014 - GE Cour de justice (2014)
NOUVEAU MOYEN DE FAIT; ENQUÊTE PÉNALE; COMPLÉMENT; INDEMNITÉ(EN GÉNÉRAL); FAUTE PROPRE | CPP.310.1; CP.173; CP.180; CP.181; CPP.323; CPP.428; CPP.436; CPP.433